Sexual differences in the consumption of food by Homo sapiens: some speculations in archeogastronomy and the evolution of eating patterns - Pont, Graham (Universidad Estatal a Distancia, Costa Rica, 2012)
En las sociedades tradicionales, los hombres son más propensos aconsumir grandes cantidades de alimentos en unas pocas comidasdiarias, mientras que las mujeres tienden a consumir pequeñascantidades de comida, pero con más frecuencia durante el día. Aquípropongo la hipótesis de que este comportamiento tiene una basebiológica, porque en las sociedades de cazadores-recolectores, loshombres hacían la caza en grandes áreas y comían abundantementeal obtener una presa, mientras que las mujeres se movían en unazona más restringida, recolectaban y con frecuencia comían de lospequeños alimentos hallados. Sugiero que en el sentido gastronómico,la orientación del hombre es extra-territorial y la orientación de la mujeres predominantemente intra-territorial.ABSTRACT In traditional societies, men are more likely to consume substantialamounts of food in a few daily meals, whereas women tend to consumesmaller quantities of food but to do it more frequently during the day.Here I propose the hypothesis that this behavior has a biological basisbecause in hunting-gathering societies, it was the men who did thehunting over large areas and had to wait until a kill was made to eat(often a large amount of food in a single sitting), while women movedin a more restricted area, did the gathering and frequently ate some ofthe small pieces of food that they found. I suggest that in gastronomicand spatial terms, the orientation of the male is extra-territorial and theorientation of the female is predominantly intra-territorial.